NUMERICALANALYSIS of MECHANICAL DISTORTIONBEHAVIOR of MULTIMATERIAL PRODUCTSWITH BLOCK FORMATIONCu-Ni - Amat Umron; Susilo Adi Widyanto (ICETIA, 2016)
Abstract—The setting of physical and mechanical behavior of aproduct increasingly necessary to improve the economical aspects.One applicative techniques that can be done is the incorporation ofthe material making up a product with variations in the type andposition. This study models the bimetal products by varying theposition of the combination block Cu-Ni. Simulation using FiniteElement Method (FEM), the results obtained in the form of deflectionand twist angle. From the simulation results obtained smallestdeflection occurs in combination model block length and deflectionCu-Ni greatest model of Cu-Ni horizontal position. While thesmallest torsional angle for temperature occurs in a wide combinationmodel block Cu-Ni and greatest torsional angle occurs in blocks widevariation model combination Cu-Ni.